The effect of promotion and service quality on purchase decisions with price as a mediation variable at wizzmie in surakarta city - Janothama, Fauzan; Saputro, Edy Purwo (Institute of Computer Science (IOCS), 2026)
This study examines the influence of promotion and service quality on consumers’ purchase decisions at Wizzmie in Surakarta, with perceived price positioned as a mediating variable. A quantitative approach was employed, collecting primary data through a structured questionnaire distributed to consumers with verified purchasing experience using purposive sampling. All constructs were measured with a five-point Likert scale and analyzed using SmartPLS, which included measurement model assessment and structural model testing with bootstrapping procedures. The findings indicate that promotion does not directly influence purchase decisions, while service quality and perceived price demonstrate significant effects. The results also show that both promotion and service quality significantly affect perceived price, which in turn mediates their indirect influence on purchase decision-making. These findings suggest that perceived value plays a pivotal role in shaping consumer behavior. Practically, the results imply that marketers should design promotional strategies that strengthen price perception for example through discount bundles, loyalty programs, and targeted offerings. The study is geographically limited to Surakarta; therefore, future research is recommended to expand sample coverage and explore alternative promotional variables.